Sustained low prevalence of meticillin-resistant Staphylococcus aureus upon admission to hospital in The Netherlands - Bode, L; Wertheim, H; Kluytmans, J; Bogaers-Hofman, D; Vandenbroucke-Grauls, C; Roosendaal, R; Troelstra, A; Box, A; Voss, A; van Belkum, A; Verbrugh, H; Vos, M (2011)
The prevalence of meticillin-resistant Staphylococcus aureus (MRSA) carriage at hospital admission in The Netherlands was 0.03% in 1999-2000. The aim of the present study was to assess whether the prevalence of MRSA carriage in The Netherlands has changed over the last few years. In five Dutch hospitals, 6496 unique patients were screened for nasal S. aureus carriage at hospital admission by microbiological culture between 1 October 2005 and 7 June 2007. In total, 2036 of 6496 (31.3%) patients carried S. aureus in their nose, and seven of 6496 (0.11%) patients were nasal carriers of MRSA. Compared with 1999-2000, the prevalence of MRSA carriage in the Dutch population at hospital admission has increased more than three fold; however, this increase was not significant (P= 0.06, Fisher's exact test). This prevalence is still among the lowest in the world, probably as a result of the stringent Dutch infection control policy, and the restrictive use of antibiotics in The Netherlands. © 2011 The Healthcare Infection Society.